Production and shedding of Erianthus arundinaceus roots revealed by ingrowth core method. (20th November 2015) - Sekiya, Nobuhito; Abe, Jun; Morita, Shigenori
Abstract: Erianthus arundinaceus is a potential feedstock for biofuel production. In material crops cultivation, roots are a major source of organic matter incorporated into the soil and greatly influence soil fertility. Here, we quantified root production and shedding of 3‐year‐old E. arundinaceus plants in Tokyo. Sequential sampling of ingrowth cores revealed that E. arundinaceus actively produced new roots from June to October. The active phase of root production followed the rapid growth period of shoot parts, suggesting a shift of assimilate allocation from the shoot to root in June. Measurements of standing roots before and after the ingrowth core sampling allowed us to estimate that roots shed dry matter of 162.6 g m −2 during the growing season. This value was comparable to that of plant residues, including the shoots, of some common crop species, suggesting that E. arundinaceus root shedding supplies sufficient organic matter to sustain soil fertility.